Contesting images in the (re)construction of ethnic identities: The case of Huarpe community in Argentina - Nussbaumer, Beatriz Brigida (2015)
This chapter analyses the perceptions natives from a rural community in the region of the Lavalle Desert (Mendoza Province, Argentina) have of their territory. Framed in an ethnic (re)articulation process, the dispute for identity recognition as well as for the land they historically occupied, promotes a (re)signification process local people perform on their past. Thus, the appropriation modes of territory and notions of community are also revisited. The use of photo-elucidation technique based on photographs taken by local participants, allowed us to identify the significance they attribute to i) the natural and cultural space, ii) to the social practices and iii) to the community, in the production of meanings of their territory. Either the self-valuation of time-space territorial knowledge, as well as the positive inversion of the term desert as a stigma, both intervened in the reaffirmation of their identity and the legitimacy their claims.